Disease monitoring of biologic treatment in IBD: early impact and future implications of COVID-19 pandemic. Issue 4 (30th September 2020) - Shields, Stephanie; Dunlop, Allan; Seenan, John Paul; Macdonald, Jonathan
Abstract : COVID-19 has dominated life in 2020 with, at the time of writing, over 4.9M global cases and >320 000 deaths. The impact has been most intensely felt in acute and critical care environments. However, with most UK elective work postponed, laboratory testing of faecal calprotectin halted due to potential risk of viral transmission and non-emergency endoscopies and surgeries cancelled, the secondary impact on chronic illnesses such as inflammatory bowel disease (IBD) is becoming apparent. Data from the Scottish Biologic Therapeutic Drug Monitoring (TDM) service shows a dramatic drop in TDM testing since the pandemic onset. April 2020 saw a 75.6% reduction in adalimumab testing and a 36.2% reduction in infliximab testing when compared with February 2020 data, a reduction coinciding with the widespread cancellation of outpatient and elective activity. It is feared that disruption to normal patterns of care and disease monitoring of biologic patients could increase the risk of disease flare and adverse clinical outcomes. Urgent changes in clinical practice have been instigated to mitigate the effects of the pandemic on routine clinical care. Further transformations are needed to maintain safe, effective, patient-centred IBD care in the future.